Outcome after surgery for acute type A aortic dissection with or without primary tear resection - Uimonen Mikko; Olsson Christian; Jeppsson Anders; Geirsson Arnar; Chemtob Raphaelle; Khalil Ahmad; Hjortdal Vibeke; Hansson Emma C; Nozohoor Shahab; Zindovic Igor; Gunn Jarmo; Wickbom Anders; et al. (United States, 2022)
Background: The outcome in patients after surgery for acute type A aortic dissection without replacement of the part of the aorta containing the primary tear is undefined.
Methods: Data of 1122 patients who underwent surgery for acute type A aortic dissection in eight Nordic centers from Jan 2005 to Dec 2014 were retrospectively analyzed. The patients with primary tear location either unfound, unknown, not confirmed or not recorded (n=243, 21.7%) were excluded from the analysis. The patients were divided into two groups according to whether the aortic reconstruction encompassed the portion of the primary tear (TR group, n=730) or not (TNR group, n=149). The restricted mean survival time ratios adjusted for patient characteristics and surgical details between the groups were calculated for all-cause mortality and aortic reoperation-free survival. The median follow-up time was 2.57 (inter-quartile range 0.53-5.30) years.
Results: For the majority of the patients in the TR group, the primary tear was located in the ascending aorta (83.6%). The reconstruction encompassed both aortic root and the aortic arch in 7.4% in the TR group as compared with 0.7% in the TNR patients (P<0.001). There were no significant differences in all-cause mortality (adjusted restricted mean survival time ratio 1.01, 95% confidence interval 0.92-1.12, P=0.799) or reoperation-free survival (adjusted restricted mean survival time ratio 0.98, 95% confidence interval 0.95-1.02, P=0.436) between the TR group and TNR groups.
Conclusions: Primary tear resection alo